PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK TERHADAP MOTIVASI BELAJAR PKn SISWA KELAS III SDN 188 PEKANBARU - Cindy Triwulan Desta; Eddy Noviana; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research aims to know the differences of learning motivation that learned through talking stick model of learning and the students that learned through lecture. This research uses quasi experimental method with nonequivalent control group design. This research was conducted in SDN 188 Pekanbaru in academic year 2017/2018 with grade III A as control class and grade III C as experiment class. The data for learning motivation were gathered by using questionnaire. The data were analyzed by using Microsoft Excel with t-test analyzed (independent t-test). The results showed is in pretest obtained was average of experimental class was 70.48 and control class was 70.32 the t-test obtained was =tcount = 2.706 > ttabel = 2.000. and in the posttest there are differences in learning motivation students that learned through talking stick model and students that learned through lecture methods. The average of experimental class was 75.61 and control class was 70.74 the t-test obtained was =tcount = 2.706 > ttabel = 2.000.Key Word: Talking Stick, learning motivation